Prevalence of urinary tract infection among patient at Hospital Sultan Abdul Halim (HSAH) based on gender and age / Nurfatini Husna Mohd Afdiiza - Mohd Afdiiza, Nurfatini Husna (2015)
The aim of the present study was to determine the prevalence of urinary tract infection based on gender and age. Urinary tract infections (UTIs) are among the most common bacterial infections in humans both in community and hospital settings. The data collections were obtained from Microbiology department of Hospital Sultan Abdul Halim and the result were analysed using the Graphpad instat. The data were collected from January 2015 until June 2015. From the result, the risk of female getting urinary tract infection is highest than male. The result also shows that the most affected age with urinary tract infection is between 51-70 years old and the least age is between 15-30 years old. Bacterial isolates were identified based on colonial morphology, microscopic characteristics, and biochemical tests. Escherichia coli are the most predominant organism 118(38%). This was followed by 42(13%) of Klebsiella pneumonia. Candida albican 34(11%), Candida sp. 34(11%), Streptococcus 17(5%), Enterococcus 13(4%) and Others 56(18%). In conclusion, UT1 can cause morbidity and mortality to the affected person if is not treated properly. Antibiotic usage has proven to be beneficial treatment for the urinary tract infection.